ORIBATID MITES (ACARIÑA: ORIBATIDA) IN THE HIGH ALTITUDE MEADOWS, FROM THE ANDES RANGE, CENTRAL PART, CHILE (Acta Entomológica Chilena, 2022)
The oribatid fauna was studied in the altitude marshy meadows (3,200 mosl) with cushion like vegetaron, in the Andes Range, central part of Chile (Región Metropolitana). 18 species were determined, among which 5 species were not known to occur in Chile; 2 species are probably new to Science.
Keywords: Oribatid mites, High altitude meadows, Chile